On the use of symmetry in SCF calculations. The case of fullerenes and nanotubes - Zicovich-Wilson, C.; Noel, Y.; Ferrari, A.; Orlando, R.; De La Pierre, Marco; Dovesi, R. (AIP Publishing, 2012)
The way point symmetry can be exploited to reduce the computational cost (CPU time and memory allocation) in SCF ab initio calculations is discussed. Crucial for the CPU time are the calculation of the mono- and bi-electronic integrals and the diagonalization of the Fock matrix at selected points in reciprocal space; as regards memory allocation, the full square density and Fock matrices must be avoided. Quantitative examples are given in the case of high symmetry compounds such as carbonfullerenes and nanotubes.